PESAN DAKWAH DALAM LINE WEBTOON “KOLANG-KALING” EPISODE SEMBILAN (9) - Sunrise (EDISI RAMADHAN 2021) - Hadi Ismanto; Nor Azizah Safitri (Indonesian Journal of Islamic Communication, 2021)
Various media can be used in the implementation of da'wah, such as comics. In the month Ramadhan 2021, LINE Webtoon published a new webtoon with the title "Kolang-Kaling". In this study, researchers are interested in the webtoon "Kolang-Kaling", especially in episode nine (9) - Sunrise, because in this episode it is full of exposure to three types of da'wah material that can be used as da'wah messages, namely: akhlak, aqidah, and syari’ah. This study uses an approach with a descriptive type of research. Analysis of the data used in this study using content analysis. Based on the results of the research, the researcher hopes that readers, apart from enjoying the art, can also take the messages contained in the webtoon. In addition, Islamic webtoons like this can be reproduced and used as a media of da'wah, so that they can take advantage of webtoon readings that are less educational